Uma investigação acerca das harmônicas não características no contexto da geração eólica - Azevedo Júnior, Celso Rosa de (2020)
From the recent researches related to sustainable energy exploitation, it is evident that wind energy has been taking an important role in the Brazilian and world energy matrix. Therefore, when considering its integration into the electric system, the literature presents possible impacts on the power quality, especially those related to the injection of harmonic currents into the system by wind turbines. In this context, the operating conditions of the connecting network may imply the emergence of non-characteristic harmonic content in the wind turbine current frequency spectrum, especially those with low-frequency harmonic orders. From this scenario, this work focuses on the exploration of the main factors that impact the generation, increase, decrease and propagation of harmonic distortions from DFIG wind turbines, which is the most used technology in wind power generation. Thus, firstly, the motivation and justification of the theme are presented in general, exposing the Brazilian transmission system conditions concerning the level of harmonic distortions. Then, the-state-of-the-art of the subject is detailed, emphasizing the investigation of non-characteristic harmonics and the main factors that influence their emergence. Later, an analysis of the main components with nonlinear characteristics in a DFIG wind turbine is also performed in order to highlight relevant aspects of its control and operation, focusing on the verified harmonic spectral content. Following the development of the research, it is developed a computational modeling of a wind farm, which operates in the northeastern of Brazil. In addition, the main conditions for the computational case studies are presented, which aim to investigate the cause of the emergence of non-characteristic harmonics in the context of wind power generation.